2021
DOI: 10.1021/acs.jced.0c00933
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria of the Synthesized Ternary CH4/CO2/N2 Mixed-Gas Hydrates in Tetrabutylammonium Bromide Aqueous Solutions at Different Concentrations

Abstract: Hydrate-based gas separation (HBGS) technology can effectively separate CH 4 and CO 2 in multicomponent gases. To provide the necessary basic data for the HBGS technology, the hydrate phase equilibrium conditions of a ternary gas mixture (CH 4 /CO 2 /N 2 = 0.5/0.4/0.1) were determined and compared in tetrabutylammonium bromide (TBAB) aqueous solutions with different mass fractions (0.05, 0.1, 0.2, and 0.4). The results indicated that all four concentrations of TBAB aqueous solution could shift the hydrate phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…To determine the effect of the mixed gas additives, the hydrate phase equilibrium data were analyzed under different conditions (Figure ). As reliable experimental results were previously obtained using this experimental device, the accuracy of the equipment was not verified in this work.…”
Section: Results and Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…To determine the effect of the mixed gas additives, the hydrate phase equilibrium data were analyzed under different conditions (Figure ). As reliable experimental results were previously obtained using this experimental device, the accuracy of the equipment was not verified in this work.…”
Section: Results and Discussionmentioning
confidence: 85%
“…The experiment was carried out on a self-made system. This device has been used and described in a prior literature report . The main component of the device is a high-pressure reactor with sight windows on both sides, with a mechanical stirring system placed inside the reactor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deschamps and Dalmazzone found that high concentrations of TBA salts can enlarge the CH 4 /CO 2 hydrate stability zone [7]; however, these concentrations may be unfavorable for the separation of CO 2 from mixtures of gases [8]. It has been shown that the phase equilibrium temperature of gas captured from the semi-clathrate phase increased by a range of ~9-14 K compared to that of gas hydrate formed from a pure water system when the TBAB mass fraction was 0.4 [9]. Cryo-SEM images have shown that the specific surface area of the hydrate crystals significantly increased by adding TBAB, as compared to a pure water system [10].…”
Section: Introductionmentioning
confidence: 99%
“…It can effectively improve the phase equilibrium temperature of a gas hydrate with the addition of a certain concentration of the TBAB aqueous solution under the condition of a same pressure . While Zang et al proposed that the effectiveness of the concentration increase under the phase equilibrium condition promotion for a CH 4 /CO 2 /N 2 ternary gas mixture hydrate is not obvious anymore. Liang and his team also confirmed that TBAB can increase the phase equilibrium temperature of the CO 2 hydrate under a certain pressure.…”
Section: Introductionmentioning
confidence: 99%